الإشتراط في عقد الزواج في قانون الأسرة الجزائري - يوسف مزيان (My University, 2024)
Abstract: The research aims to talk about the stipulation in the marriage contract, in the Algerian family law, and to what extent has the legislator agreed to regulate the stipulation process, and what are the consequences of not fulfilling the conditions? By studying and analyzing articles 19, 32, 35 of the family law, and the position of Islamic jurisprudence, fro; the issue of conditionality. The research concluded that the legislator took into account the stability of the family and the preservation of its cohesion by permitting the conditions associated with the contract, and granting the right of annulation, divorce, and compensation to the wife if the husband did not fulfill the conditions. ....................... الملخص: يهدف البحث إلى الحديث عن الاشتراط في عقد الزواج في قانون الأسرة الجزائري، وإلى أي مدى وفق المشرع في تنظيم عملية الاشتراط، وما الآثار المترتبة على عدم الوفاء بالشروط؟، وذلك بدراسة وتحليل المواد 19، 32، 35، من قانون الأسرة، وموقف الفقه الاسلامي من مسألة الاشتراط. وقد خلص البحث إلى أن المشرع راعى استقرار الأسرة، والحفاظ على تماسكها، وذلك بإباحة الشروط المقترنة بالعقد، ومنح حق الفسخ والتطليق والتعويض للزوجة إذا لم يف الزوج بالشروط. ........................ Résume : La recherche vise à parler de la stipulation du contrat de mariage dans le droit de la famille algérien, et dans quelle mesure le législateur a-t-il accepte de règlementer le processus de stipulation, et quelles sont les conséquences du non-respect des conditions, en étudiant et en analysant les articles 19, 32, 35 du droit de la famille et la position de la jurisprudence islamique sur la question de la conditionnalité. La recherche a conclu que le législateur a prise en compte la stabilité de la famille et la préservation de sa cohésion en autorisant les conditions associées au contrat et en accordant le droit à l'annulation, au divorce et a l'indemnisation à l'épouse si le mari ne remplissait pas les conditions.